MANAJEMEN PENINGKATAN KUALITAS SANTRI PONDOK PESANTREN AL-JAUHAREN KOTA JAMBI (STUDI TERHADAP GAYA KEPEMIMPINAN USTADZ ALWI MAHFUDZ) - Sukardi, Sukardi; Jamaluddin, Jamaluddin; Zulqarnin, Zulqarnin (UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research is motivated by the efforts of the Aljauharen Islamic Boarding School, as a religious institution, to educate its students and alumni to maintain manners and morals. These efforts have attracted the public's interest in enrolling their children in the Aljauharen Islamic Boarding School, Jambi City. This research aims to determine the form of management of the Aljauharen Islamic Boarding School in Jambi City, examine the supporting and inhibiting factors in the management of the Aljauharen Islamic Boarding School in Jambi City and examine the leadership management of Ustadz Alwi Mahfudz in improving the quality of student graduates of the Aljauharen Islamic Boarding School in Jambi City.This research uses qualitative research methods. Data collection techniques through interviews, observation and documentation. Interviews were conducted with six informants, namely the leadership, two administrators, and three alumni directly. Meanwhile, observations were carried out from May to July 2023